2023
DOI: 10.3390/pharmaceutics15020562
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Inhibitory Effects of Bovine Lactoferrin on Invasion of Oral Squamous Cell Carcinoma

Abstract: Lactoferrin (LF), an iron-binding glycoprotein, has been reported to have anticancer properties. However, the molecular mechanisms behind its anticancer effects on oral squamous cell carcinoma (OSCC) have not yet been elucidated. Therefore, we aimed to clarify the effects of LF on invasion of OSCC, and its underlying molecular mechanism. OSCC cell lines, HSC2 and HOC313, were treated with bovine LF (bLF). The effects of bLF on cell invasion were examined by a chamber migration assay, wound healing assay, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…LfR was identified as a specific receptor of human LF that associates with AP2, which mediates internalization via clathrin endocytosis to stimulate ERK signaling (Jiang et al., 2011 ). The low‐density lipoprotein receptor‐related protein (LRP‐1) is a major endocytic receptor known to bind more than 35 ligands with signaling properties (Etique et al., 2013 ), and different evidences suggest that LRP‐1 could be a likely bLF receptor in different models (Chea et al., 2023 ; Takayama et al., 2003 ). After binding to LRP‐1, bLF promoted the phosphorylation of Akt1 and extracellular signal‐regulated protein kinase (ERK1/2); an induction process that requires iron‐saturated bLF (holo‐LF) (Ryu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…LfR was identified as a specific receptor of human LF that associates with AP2, which mediates internalization via clathrin endocytosis to stimulate ERK signaling (Jiang et al., 2011 ). The low‐density lipoprotein receptor‐related protein (LRP‐1) is a major endocytic receptor known to bind more than 35 ligands with signaling properties (Etique et al., 2013 ), and different evidences suggest that LRP‐1 could be a likely bLF receptor in different models (Chea et al., 2023 ; Takayama et al., 2003 ). After binding to LRP‐1, bLF promoted the phosphorylation of Akt1 and extracellular signal‐regulated protein kinase (ERK1/2); an induction process that requires iron‐saturated bLF (holo‐LF) (Ryu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the milk protein lactoferrin works to prevent cancer progression through iron chelation by competing with transferrin, which is in the same family of proteins ( 41 , 42 ). Owing to the solid inhibitory power of lactoferrin against plasmin ( 43 , 44 ), its cancer prevention effect may be ascribed to both chelation of iron (a vital cancer nutrient) and inhibition of plasmin. These results emphasize that cell surface plasmin is a potent druggable target for the prevention of life-threatening cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the anticancer efficacy of a PP other than CPPs (TP10 and NHP) combined with antibiotics, we selected lactoffericin B (LfcinB), an AMP with established anticancer activity and low toxicity [47][48][49][50][51][52][53][54]. LfcinB is a shorter version of lactoferrin, and like the original peptide, it demonstrates anticancer properties [55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%